2021
DOI: 10.1038/s41699-021-00269-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design for the ballistic diode based on graphene field-effect transistors

Abstract: We investigate the transport behavior of two-terminal graphene ballistic devices with bias voltages up to a few volts suitable for electronics applications. Four graphene devices based ballistic designs, specially fabricated from mechanically exfoliated graphene encapsulated by hexagonal boron nitride, exhibit strong nonlinear I-V characteristic curves at room temperature. A maximum asymmetry ratio of 1.58 is achieved at a current of 60 µA at room temperature through the ballistic behavior is limited by the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…5 The simple tapered shape devices were studied in another work that reported dependence of DC asymmetric current on neck width and MFP. 33 The DC output voltage between electrodes 2 and 4 was expected in ballistic transport regime for various V g around the neutrality point (V D ) V D = −1 V. As shown in Figure 3b, the output voltages V 24 versus input current were measured at the various V g in the current range of I 13 between −20 μA and +20 μA. Parabolic I− V curves were obtained as a characteristic behavior of ballistic rectifying devices.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…5 The simple tapered shape devices were studied in another work that reported dependence of DC asymmetric current on neck width and MFP. 33 The DC output voltage between electrodes 2 and 4 was expected in ballistic transport regime for various V g around the neutrality point (V D ) V D = −1 V. As shown in Figure 3b, the output voltages V 24 versus input current were measured at the various V g in the current range of I 13 between −20 μA and +20 μA. Parabolic I− V curves were obtained as a characteristic behavior of ballistic rectifying devices.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The ratcheting effect could contribute additional rectification due to the tapered shapes of each arm (Figure a) . The simple tapered shape devices were studied in another work that reported dependence of DC asymmetric current on neck width and MFP . The DC output voltage between electrodes 2 and 4 was expected in ballistic transport regime for various V g around the neutrality point ( V D ) V D = −1 V. As shown in Figure b, the output voltages V 24 versus input current were measured at the various V g in the current range of I 13 between −20 μA and +20 μA.…”
Section: Cross-junction Characterizationmentioning
confidence: 96%
“…This simulation indicates that the overall trend of T is in agreement with the A properties of graphene devices, as conrmed by some previous studies. 32,56 It is worth noting that the harvesting efficiency of antennas has been discussed by several authors in recent years. While Midrio et al 57 referred to receiving efficiency in antennas, some previously published papers focused on transmission and reection efficiencies.…”
Section: Transmission Spectra (T)mentioning
confidence: 99%
“…The results demonstrated an asymmetric graphene diode with an A of 1.16 possessed better rectifier efficiency than a symmetric device with an A of 0.5. Nguyen 32 evaluated four AGD structures by mechanical changes in their geometry, including neck length and the direction of the current. In a study based on experimental observation and numerical simulations, they reported different A values for different types of ballistic device.…”
Section: Introductionmentioning
confidence: 99%
“…In the optimization of analog circuits, the optimization of the circuit structure is mainly done by various methods to improve the circuit structure and to find a circuit form with lower delay and higher efficiency. Optimization of analog circuits relies on the experience and intuition of engineers to find the right parameters to meet the requirements of the circuit, which is time-consuming and costly [19]. Therefore, it is essential to find suitable methods to optimize circuits quickly.…”
Section: Optimization Of Circuit Structuresmentioning
confidence: 99%